PROBLEMS OF CONSTITUTIONAL LAW OF THE EUROPEAN UNION - Mark Voronov; Izabella Voronova (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право», 2022)
Introduction. The article examines the most important aspects of the issues of EU constitutional law, namely the nature of European constitutionalism, European values and identity, the relationship between the optimal European model and global governance. The author substantiates the opinion that, for the first time in the process of European integration, today it is possible to notice a discrepancy between the "material" and "legal" Constitution. Therefore, it seems to be a valid position regarding the possibility of revising the treaties that make up the current Constitution of Europe. Interdisciplinary and institutionalized research among academics on current issues of EU constitutional law, in particular, the current state of the European constitutional process, its possible evolution and potential application to global governance can contribute to making the current debate on the future of the EU and international relations more effective. Although the European constitutional process today has certain flaws, the EU has nevertheless managed to legitimize itself through the affirmation of an identity that synthesizes democratic values and citizenship status for Europeans.